Copper Complexes as Anticancer Agents - Marzano, Cristina; Pellei, Maura; Tisato, Francesco; Santini, Carlo (Anti-Cancer Agents in Medicinal Chemistry, 2009)
Metal-based antitumor drugs play a relevant role in antiblastic chemotherapy. Cisplatin is regarded as one of the most effective drugs, even if severe toxicities and drug resistance phenomena limit its clinical use. Therefore, in recent years there has been a rapid expansion in research and development of novel metal-based anticancer drugs to improve clinical effectiveness, to reduce general toxicity and to broaden the spectrum of activity. The variety of metal ion functions in biology has stimulated the development of new metallodrugs other than Pt drugs with the aim to obtain compounds acting via alternative mechanisms of action. Among non-Pt compounds, copper complexes are potentially attractive as anticancer agents. Actually, since many years a lot of researches have actively investigated copper compounds based on the assumption proposal that endogenous metals may be less toxic. It has been established that the properties of copper-coordinated compounds are largely determined by the nature of ligands and donor atoms bound to the metal ion. In this review, the most remarkable achievements in the design and development of copper(I, II) complexes as antitumor agents are discussed. Special emphasis has been focused on the identification of structure-activity relationships for the different classes of copper(I,II) complexes. This work was motivated by the observation that no comprehensive surveys of copper complexes as anticancer agents were available in the literature. Moreover, up to now, despite the enormous efforts in synthesizing different classes of copper complexes, very few data concerning the molecular basis of the mechanisms underlying their antitumor activity are available. This overview, collecting the most significant strategies adopted in the last ten years to design promising anticancer copper( I,II) compounds, would be a help to the researchers working in this field.
Keywords: antitumor activity